The Role of Educational Management in School Human Resource Loyalty: An Analysis at SMP Darussalam Syafaat - Muhammad Taufiq; Ahmad Sodik; Ahmad Dawam (Jurnal Manajemen Pendidikan Islam Darussalam, 2026)
The importance of strengthening the managerial process, namely planning, organizing, implementing, and supervising, is to foster commitment and retention of school human resources. This study employed a quantitative explanatory method through a total sampling survey (N=30) using a 4-point Likert scale questionnaire, accompanied by documentation, observation, and supporting interviews. The instrument met the valid-reliable criteria (?: X=0.870; Y1=0.774; Y2=0.756), and the data passed the Shapiro–Wilk normality test (p>0.05); hence, parametric analysis was conducted. Simple linear regression showed a positive and significant effect of educational management on teacher loyalty (Y1: R=0.363; R2=0.132; ?=0.227; F=4.243; p=0.049) and staff loyalty (Y2: R=0.392; R2=0.154; ?=0.215; F=5.083; p=0.032). These findings confirm that sharpening planning and performance communication, reward systems, and career development, as well as structuring SOPs and internal services, fostering an engagement culture, and maintaining continuous supervision are practical levers to enhance loyalty. The recommendations aim to strengthen two-way communication, ensure fair and transparent rewards, implement professional development programs, and digitalize internal service processes, thereby improving the impact on loyalty and making it stronger and more sustainable.